2010
DOI: 10.1128/mcb.00394-10
|View full text |Cite
|
Sign up to set email alerts
|

Ric-8A and Giα Recruit LGN, NuMA, and Dynein to the Cell Cortex To Help Orient the Mitotic Spindle

Abstract: In model organisms, resistance to inhibitors of cholinesterase 8 (Ric-8), a G protein ␣ (G␣) subunit guanine nucleotide exchange factor (GEF), functions to orient mitotic spindles during asymmetric cell divisions; however, whether Ric-8A has any role in mammalian cell division is unknown. We show here that Ric-8A and G␣ i function to orient the metaphase mitotic spindle of mammalian adherent cells. During mitosis, Ric-8A localized at the cell cortex, spindle poles, centromeres, central spindle, and midbody. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
174
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 39 publications
16
174
0
5
Order By: Relevance
“…Although, the RIC-8 expression in the embryonic tissues is clearly detectable by immunohistochemistry only from the beginning of the gastrulation, the earlier growth retardation of the Ric-8 À/À mutant embryos, compared to the control littermates, may be due to the interfered mitotic division. This speculation is in line with the experiments in HeLa cells, where the reduced expression of RIC-8A was shown to prolong mitosis, cause occasional mitotic arrest, and decreased movement of the spindle (Woodard et al, 2010).…”
Section: Development Of Ric-8 2/2 Embryos Is Retardedsupporting
confidence: 84%
See 3 more Smart Citations
“…Although, the RIC-8 expression in the embryonic tissues is clearly detectable by immunohistochemistry only from the beginning of the gastrulation, the earlier growth retardation of the Ric-8 À/À mutant embryos, compared to the control littermates, may be due to the interfered mitotic division. This speculation is in line with the experiments in HeLa cells, where the reduced expression of RIC-8A was shown to prolong mitosis, cause occasional mitotic arrest, and decreased movement of the spindle (Woodard et al, 2010).…”
Section: Development Of Ric-8 2/2 Embryos Is Retardedsupporting
confidence: 84%
“…This tertiary complex initially localizes at the cell cortex, where the dynamic release of NuMA from LGN may promote aster microtubule pulling during cell division (Du et al, 2002;Du and Macara, 2004). A very recent study demonstrated that RIC-8A is necessary for the assembly of a cortical signaling complex that orients the mitotic spindle during mammalian cell division (Woodard et al, 2010). The expression pattern of RIC-8 characterized in our study lets us assume that it is involved in the cell division in developing ectoderm during mouse gastrulation.…”
Section: Expression Of Ric-8 During Early Embryogenesis Of Mousesupporting
confidence: 51%
See 2 more Smart Citations
“…In cells with supernumerary centrosomes that exhibit clustering, the net force exerted on each centrosome by motor proteins may point to one or the other of two poles. Nonhomogenous distribution of dynein/dynactin, as has been found in HeLa cells, 116,117 and/or cortical cues 91 could orient the force vectors toward one or the other pole. Clustering would then be accomplished by virtue of the various centrosomes having a common final destination.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 95%